(untitled) (International Journal of Food and Nutritional Sciences, 2023)
By analyzing this paper, we discuss the theme of communication barriers through Jhumpa Lahiri’s work. Basically, communication barriers mean cultural differences which are common in Lahiri’s work. This study will explore how cultural and national identities are depicted in the characters whom Lahiri situates in a liminal space between nation and identity, embodying multiple cultures and histories. There are two works of Jhumpa Lahiri for discussion in this particular research paper- 1) The Interpreter of Maladies (1999) 2) The Namesake (2003), in which she intricately weaves the challenges faced by diasporic individuals through linguistic, cultural and emotional barriers which create alienation, misunderstandings and a lot of struggles with identity for her characters. This study also highlights how the unspoken words in Lahiri’s narratives shape the lives of her characters, reflecting universal themes of human connection and belonging in a diasporic context.